Application of Mobile Technology in College English Vocabulary Teaching. (16th February 2022) - He, Bing
Abstract : In order to improve the quality of college English vocabulary teaching, this paper studies the application of mobile technology in college English vocabulary teaching. The advantages of mobile technology are analyzed, and different mobile technology communication deployment schemes are determined according to different needs and environments of English vocabulary learning, so as to build a college English vocabulary teaching system, which is mainly composed of the user layer, mobile network layer, and English vocabulary data layer. Among them, the main functions of the user layer are user login, system information setting, English vocabulary resource browsing, uploading English vocabulary homework, etc., and determine user preference data through user logs. The mobile network layer is designed using mobile technology to create the delay control technique of the system mobile communication, and the system mobile network layer's LAN is set up to increase data transmission speed. Finally, set up the database according to the English vocabulary of English words field, calculating Euclidean distance to determine the relationship between them, and then through random set classification vocabulary data types, calculate the similarity degree of the data extraction vocabulary data characteristics and remove high similarity of the English vocabulary data to reduce the difficulty of system storage. The experimental findings suggest that the mobile technology-based system has high performance and dependability and may be widely used in practice.